2020
DOI: 10.1186/s12955-020-01561-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unilateral and bilateral laparoscopic surgery for endometriosis on Anti-Mullerian Hormone (AMH) level after 3 and 6 months: a systematic review and meta-analysis

Abstract: Background Endometriosis is one of the most common causes of infertility. The causes of the disease and its definitive treatments are still unclear. Moreover, Anti-Mullerian Hormone (AMH) is a glycoprotein dimer that is a member of the transient growth factors family. This research work aimed to identify the effect of unilateral and bilateral laparoscopic surgery for endometriosis on AMH levels after 3 months, and 6 months, using meta-analysis. Methods In this study, the articles published in national and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…However, the damage inflicted by surgery may also be due to the related local inflammation or vascular compromise secondary to excessive manipulation of the cortex with subsequent tearing, bleeding, and the need for electrosurgical coagulation ( 159 ). Five meta-analyses showed a significant reduction in serum AMH concentrations after surgical treatment of endometriomas ( 160 162 ) and this effect is persistent post-operatively up to 18 months ( 162 ) and more pronounced in case of bilateral adnexal surgery ( 163 165 ). In contrast, two meta-analyses showed that ovarian reserve evaluated by AFC is not decreased after surgical treatment of endometriomas ( 162 , 166 ).…”
Section: Pathophysiology Of Endometriosis Associated Infertilitymentioning
confidence: 99%
“…However, the damage inflicted by surgery may also be due to the related local inflammation or vascular compromise secondary to excessive manipulation of the cortex with subsequent tearing, bleeding, and the need for electrosurgical coagulation ( 159 ). Five meta-analyses showed a significant reduction in serum AMH concentrations after surgical treatment of endometriomas ( 160 162 ) and this effect is persistent post-operatively up to 18 months ( 162 ) and more pronounced in case of bilateral adnexal surgery ( 163 165 ). In contrast, two meta-analyses showed that ovarian reserve evaluated by AFC is not decreased after surgical treatment of endometriomas ( 162 , 166 ).…”
Section: Pathophysiology Of Endometriosis Associated Infertilitymentioning
confidence: 99%
“…The effect of surgery for ovarian endometriosis on markers of ovarian reserve has been previously discussed in this article. The results of those studies [17][18][19][20][21][22]24] reinforce the ESHRE recommendation to avoid surgery for ovarian endometrioma unless required to improve endometriosis-associated pain or accessibility of follicles [2]. A study looking at the surgical treatment of endometrioma >3 cm prior to IVF found a similar CPR and LBR as in women with unexplained infertility, however this was a prospective case-control study despite identifying itself as an RCT [40].…”
Section: Surgery Prior To Medically Assisted Reproduction In Women Wi...mentioning
confidence: 84%
“…One is the space occupation of OEM cyst, and subsequent ovarian tissue fibrosis reduces the functional ovarian tissue ( 6 , 28 ). The other is that inevitable removal of unaffected ovarian tissue during the surgical excision of endometrioma cyst wall aggravates the reduction in ovarian reserve function ( 3 , 29 ). Therefore, it is the dual factors of OEM itself and laparoscopic surgery that lead to the significant decrease in ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%